Intravenous isotonic fluid challenge, and L-arginine infusion for oligoamnios and diminished fetal movements: a preliminary study - Hemmanur, Samartha Ram; Samyuktha, Illa Sai; Vasudeva, Nagashree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Utero-placental insufficiency is one of the major causes of oligoamnios and diminished fetal movements (FM). Rapid intravenous isotonic fluid infusion within the cardiovascular reserve improves tissue perfusion in all systems. We tested the hypothesis that isotonic fluid challenge may improve uteroplacental perfusion, which may, in turn improve fetal oxygenation, liquor formation, and FM. Methods: In this descriptive study, twenty-three antenatal mothers with gestational age >26 weeks, and with amniotic fluid index (AFI) <8 cm were included. Intravenous isotonic fluid challenge with 2 or 3 pints of ringer’s lactate, at the rate of 180-200 drops/minute, twice daily for 2-3days and, L-arginine infusion, 300 ml/day alternate days for 2-3 doses were given. Women were advised to take more than 3 litres of water a day. AFI was recorded once daily for 5 days, and then biweekly. The fluid challenge was repeated whenever AFI diminished <8.00 cm. AFI and perceived FM were graded. Pregnancies were terminated when there was no response to fluid challenge. The trend of changes in AFI and FM grades, number of days pregnancies continued, and perinatal outcomes were recorded. Results: We noted recurrent fall in AFI after an initial arise in 20 women, which required recurrent fluid challenges. Pregnancies could be continued for 18±8.5 days (median±SD). Three women, with case of absent FM, reported FM within 1 hour after initiation of the fluid challenge. There were no perinatal deaths. Conclusions: Intravenous isotonic fluid challenge and L-arginine infusion, improves AFI and FM, and helps to prolong pregnancies towards viability.